Prognostic Indicators Effective on Overall Survival in Bladder Carcinoma - Ünal, Doğan; Yeni, Ercan; Verit, Ayhan (Fırat University, 2001)
Aim: To investigate prognostic factors affecting cancer-specific survival in all clinical stages of bladder cancer. Materials and Methods: The study was conducted by data of 45 patients with bladder carcinoma (34 male, 76% and 11 female, 24%). Mean age was 59 (30-82). Blood hemoglobin level and blood group were determined by various clinical and laboratory examinations, and size, multiplicity, localization, appearance, clinical stage (pT stage) and pathological differentiation of tumors (PD) by imaging and endourological techniques. In addition, recurrence and progression in follow-up was recorded. The effects of all parameters on overall survival were evaluated by using univariate (Kaplan-Meier and Logrank tests), and multivariate (Cox regression model) analyses. Results: A total of 7 deaths occur in a mean followup of 38 months (18-44). Cumulative survival rate was 77%. In univariate analysis age, gender, hemoglobin level, O blood group of patients, localization of the tumor were ineffective; size of the tumor, multiplicity, pT stage, PD and progression in followup were highly effective on overall survival; Tumor appearance and recurrence in followup had borderline importance. In multivariate analysis the most significant prognostic factor was PD. Discussion and Conclusion: In our study tumor localization, generally found as an important prognostic factor in other studies, had not any prognostic significance. In addition, unlike recurrence, progression in followup was highly important in prognosis. Consequently, it was determined that the most significant indicator in poor prognosis of bladder carcinoma was PD.

Amaç: Mesane kanserinde klinik evreden bağımsız olarak hastalığa özgü sağkalım oranlarını etkileyen prognostik faktörler araştırmak. Gereç ve Yöntem: Çalışma 34'ü (%76) erkek, 11'i (%24) kadın, yaş ortalaması 59 (30-82) olan toplam 45 mesane kanserli hastanın verileriyle yapıldı. Kan hemoglobin seviyesi, kan grubu; sistoskopi ve rezeksiyondan elde edilen bilgilerle tümörün boyutu, sayısı, mesane içi yerleşimi, görünümü, klinik evresi (pT evre) ve patolojik diferansiasyon derecesi (PD) saptandı. Ayrıca takipte rekürens ve progresyon görülmesi kaydedildi. Bütün parametrelerin tüm sağkalıma etkileri univariate (Kaplan-Meier ve Logrank testleri) ve multivariate (Cox regresyon model) analizlerle değerlendirildi. Bulgular: Ortalama 38 ay (18-44) izlem süresi sırasında hastaların 7'sinde (%16) ölüm meydana gelirken kümülatif sağkalım oranı %77 olarak hesaplandı. Univariate analizlerde yaş, cinsiyet, hemoglobin, kan grubu ve tümör yerleşiminin sağkalım olasılığını önemli oranda etkilemediği, tümör boyutu, sayısı, pT evre, PD ve takipte progresyon gözlenmesinin tüm sağkalımı etkilediği, ancak tümör görünümü ve takipte rekürens saptanmasının sınırda bir önemle sağkalımı etkilediği saptandı. Multivariate analizde en önemli prognostik faktörün PD olduğu bulundu. Tartışma ve Sonuç: Çalışmamızda genellikle önemli bir prognostik faktör olarak gösterilen tümörün mesane içi yerleşiminin önemsiz bulunması, ayrıca rekürensin sağkalıma önemli oranda etki yapmaması karşısında progresyonun prognozu önemli oranda kötüleştirmesi dikkat çekici bulunmuştur. Mesane kanseri için en önemli prognostik faktörün ise PD olduğu saptanmıştır.
MESANE KANSERİNDE TÜM SAĞKALIM ÜZERİNE ETKİLİ PROGNOSTİK GÖSTERGELER